2022
DOI: 10.1007/s00247-022-05322-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of artificial intelligence in paediatric neuroradiology

Abstract: Imaging plays a fundamental role in the managing childhood neurologic, neurosurgical and neuro-oncological disease. Employing multi-parametric MRI techniques, such as spectroscopy and diffusion- and perfusion-weighted imaging, to the radiophenotyping of neuroradiologic conditions is becoming increasingly prevalent, particularly with radiogenomic analyses correlating imaging characteristics with molecular biomarkers of disease. However, integration into routine clinical practice remains elusive. With modern mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…However, due to the physical vulnerability of children, various treatments may be harmful to them, which makes brain tumors always be a serious challenge for physicians [8]. Due to the complexity of brain tumors in children, artificial intelligence can be useful in two directions, firstly in the diagnostic direction, where the use of artificial neural networks has made it possible to use only T-2 weighted imaging to classify medulloblastoma, diffuse midline glioma, and hairy cell astrocytoma [8]. Some success has also been achieved using decision trees to classify high-and low-grade gliomas [8].…”
Section: Brain Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, due to the physical vulnerability of children, various treatments may be harmful to them, which makes brain tumors always be a serious challenge for physicians [8]. Due to the complexity of brain tumors in children, artificial intelligence can be useful in two directions, firstly in the diagnostic direction, where the use of artificial neural networks has made it possible to use only T-2 weighted imaging to classify medulloblastoma, diffuse midline glioma, and hairy cell astrocytoma [8]. Some success has also been achieved using decision trees to classify high-and low-grade gliomas [8].…”
Section: Brain Diseasesmentioning
confidence: 99%
“…Due to the complexity of brain tumors in children, artificial intelligence can be useful in two directions, firstly in the diagnostic direction, where the use of artificial neural networks has made it possible to use only T-2 weighted imaging to classify medulloblastoma, diffuse midline glioma, and hairy cell astrocytoma [8]. Some success has also been achieved using decision trees to classify high-and low-grade gliomas [8].…”
Section: Brain Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work has shown that artificial intelligence is becoming an increasingly viable tool with the potential to improve diagnostic speed and accuracy [ 8 , 9 ]. Machine learning has already been heavily implemented in the diagnosis of brain tumors in both children and adults, with previous studies reporting algorithms that can differentiate gliomas, meningiomas, and pituitary tumors based on extracted imaging features with accuracies as high as 99% [ 10 , 11 , 12 ]. Additional work has shown the possibility of using these methods to not only differentiate between tumor types, but also to subclassify tumors by grade, stage, and even molecular features [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%